PENGARUH KONSENTRASI GULA TERHADAP KARAKTERISTIK KIMIA DAN ORGANOLEPTIK PERMEN JELLY BUAH TOMI-TOMI (Flacourtia inermis, Roxb) - Kubela, Lessy; Moniharapon, Erynola; Tuhumury, Helen C. D. (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2023)
Jelly candy has a high sugar content and a low nutritional value, but it is consumed in large quantities, particularly among children, which is harmful to their health. To make jelly candy that meets quality standards and is acceptable, different types of fruit juice will use different amounts of sugar. The goal of this study was to find the optimal sugar concentration for producing high-quality tomi-tomi jelly candy. This study employed a completely randomized design (CRD) with three levels of sugar concentration that were replicated three times, namely 50%, 100%, and 150%. The results showed that sugar concentration affected the chemical characteristics of total sugar, vitamin C content, and moisture content of tomi-tomi fruit jelly candy, but only the color characteristics from the organoleptic assessment were affected by sugar concentration. The sugar concentration of 150% was the right concentration for making tomi-tomi jelly candy with 61.51% total sugar, 26.23 mg/100g vitamin C, and 17.48% water content. This jelly candy was considered to have a red color, a tomi-tomi taste, a tomi-tomi flavor, and a chewy texture. It was preferred for its color, taste, and aroma, and was somewhat preferred for its gumminess.